Inovações tecnológicas e redes de cooperação na produção de acerola da Nova Alta Paulista - Queiroz, Timóteo Ramos [UNESP]; Pigatto, Giuliana Aparecida Santini [UNESP]; Scalco, Andréa Rossi [UNESP] (My University, 2012)
This paper had as main hypothesis of the fact that cooperation networks among producers, through the Junqueirópolis Agricultural Association, induces the innovation of process, product and management. Then, aimed to: analyze the types of cooperation networks existing in the production of acerola, describe and characterize the types of technological innovation made by producers and connect the existing networks to the occurrence of technological innovations. The descriptive and qualitative method was used, involving also the field research in two groups of producers (partnership and non-partnership). It was possible to identified and understood how to develop the process of innovation in productive activity, as well as arrangements of existing networks. Relating the characteristics of networks with the introduction of technological innovations by its partnerships, it was possible to verify the effective participation of the association induction of process innovation, product and management.
Technological innovations and cooperation networks in Nova Alta Paulista acerola production
Keywords: Cooperation; Networks, innovation, acerola